Bridging Faith and Technology: Digital Transformation of MSME Financial Transparency Through Islamic Values - Ayulestari, Isna; Dhayan , Hana (Islamic Accounting Journal, 2026)
Objective & object: This study examined the role of digital technology in enhancing financial transparency of Micro, Small, and Medium Enterprises based on Islamic values in Indonesia during 2024. Methods: An exploratory qualitative approach was employed through semi-structured interviews with six MSME owners from various sectors. Data were collected regarding their experiences with digital financial management and Islamic principles implementation, then analyzed thematically to identify patterns and challenges. Results & Conclusions: All respondents had adopted digital technologies ranging from basic spreadsheets to integrated applications, with sophistication levels correlating to business scale. Strong awareness of Islamic principles including honesty, trustworthiness, justice, and prohibition of usury was demonstrated, with three respondents reporting instances where they sacrificed profits to maintain compliance. Main challenges identified included limited digital literacy, high implementation costs, data security concerns, and scarcity of compliant technological solutions. Digital technology significantly enhanced financial transparency through automated recording, real-time reporting, and improved accountability. Limitations: The study was limited to six MSMEs in Indonesia, potentially affecting generalizability across different contexts and larger sample sizes. Implications: Findings suggest practical need for government support in developing affordable Islamic financial platforms and providing faith-based digital training. Future research should explore larger samples and specific technological solutions for Islamic compliance. Keywords: Digital transformation, financial transparency, Islamic values, MSME, Sharia compliance